Mineral drugs used in Ayurveda and Unani medicine - Vohora, S.B (Narosa, 2008)
Principal Indian systems of medicine (Ayurveda, Sidha and Unani-Tibb) use natural products (plants, animals and minerals) as drugs. While medicinal plants have received considerable attention of the scientific community. The other two categories of natural products viz of animal and mineral origin drugs have not received the requisite attention as Original Sanskrit/Arabic/Persian sources are not easily assessable. This book is the first comprehensive work covering all aspects of this subject i.e. historical, classification, single drugs and compound formulations, calcined metal preparations (42 Bhasmas and 42 Kushtas), standardization alongwith a critical review of research carried out over the last fifty years. Many useful leads suggest immense potential for development on mineral/metallic drugs internationally and further global interest in alternative therapies and trace elements.